2021
DOI: 10.1038/s41419-021-04361-9
|View full text |Cite
|
Sign up to set email alerts
|

The brain targeted delivery of programmed cell death 4 specific siRNA protects mice from CRS-induced depressive behavior

Abstract: Depression is one of the most common psychiatric disorders. Recently, studies demonstrate that antidepressants generating BDNF not only maintain synaptic signal transmission but also repress neuroinflammatory cytokines such as IL-6 and IL-1β. Therefore, promoting BDNF expression provides a strategy for the treatment of depression. Our recent research has indicated that programmed cell death 4 (Pdcd4) is a new target for antidepressant treatment by facilitating BDNF. Herein, we modified Pdcd4 specific small int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Firstly, we confirmed Pdcd4 is involved in inflammatory-related depression via regulating microglia activation. Regardless of the devasting role of neuronal Pdcd4 in chronic restraint stress (CRS)-induced depression [16,17], we found microglia Pdcd4 knockout protect mice from LPS-induced depressive-like behaviors. LPS challenge, mimicking an acute inflammatory response, stimulated peripheral immunity, and subsequently evoked neuroinflammation and depressive-like behaviors [20].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Firstly, we confirmed Pdcd4 is involved in inflammatory-related depression via regulating microglia activation. Regardless of the devasting role of neuronal Pdcd4 in chronic restraint stress (CRS)-induced depression [16,17], we found microglia Pdcd4 knockout protect mice from LPS-induced depressive-like behaviors. LPS challenge, mimicking an acute inflammatory response, stimulated peripheral immunity, and subsequently evoked neuroinflammation and depressive-like behaviors [20].…”
Section: Discussionmentioning
confidence: 86%
“…Programmed cell death 4 (Pdcd4) an apoptosis-related molecule, extensively participates in tumorigenesis and inflammatory diseases. Our previous reports have demonstrated Pdcd4 is elevated in brain of patient with depression, and neuronal-expressed Pdcd4 is involved in stress-induced depressive-like behaviors, by blocking BDNF and up-regulating proinflammatory response [16,17]. Pdcd4 has a neuroinflammatory effect on emotional disorders, however, its biological function in central nervous system (CNS) neuroinflammation remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, is there mitochondrial exchange between microglia and other types of brain cells particular neurons in AD? Recent studies reported transfer of mitochondria from astrocytes to neurons post stroke that participates in neuroprotection and neurorecovery [ 135 ]. It is interesting to examine the existence of mitochondria transportation pathway between microglia and neurons, and the biological and pathological functions of this pathway in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Much evidence suggests the synaptic plasticity dysregulation in depression aetiology, causing neuronal atrophy and synaptic weakening in critical brain regions (hippocampus and PFC). 20,21 Here, synaptic plasticity was assessed by PFC samples, western blotting and Golgi staining. which is essential for neuronal survival and brain neurogenesis and has been linked with current depression-related theories.…”
Section: Engeletin Reverses the Crs-induced Decrease In Dendritic Spi...mentioning
confidence: 99%